HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN PRESTASI AKADEMIK PADA MAHASISWA PRODI KEPERAWATAN S1 PROGRAM A ANGKATAN I STIKES RS. BAPTIS KEDIRI - Kristini, Rina Endah; Mere, Florencia Nancy (Jurnal Penelitian STIKES Kediri, 2010)
ABSTRACT Â Background : Educational succeed or achievement is one of main goal in learning process. This process has an important influence towards individuals. Academic achievement is a proof learning succeeds or individualâ€™s capability for learning activity based on credit to reach. Some individuals have problems like decreasing capability to achieve. Some factors that causes the individual has less achievement such as talent, interest, and motivation. From of three factors that influences achievement is motivation.Â Motivation is a desire, willing, and mainspring that come from inside of someone self. The objective of this research is to analyze correlation between education motivation and academic achievement to first grade student of nursing S1 program A in kediri baptist health science college Method : This research analytic cross sectional research. Data was collected using questionnaire and semester credit then analyzed statistically using â€œSpearmanâ€™s Rhoâ€ with Î± â‰¤ 0.05. showedÂ that there was correlation between education motivation and academic achievement, most respondents had high motivation, there were 25 respondents (54,35%), fair motivation, there were 19 respondents (41,30%), and less motivation, there were 2 respondents (4,35%). Conclution : The counclution be concluded that there wasÂ correlation between education motivation and academic achievement. Â Keywords: education motivation, academic achievement.